Empathy as a Predictor of Religious Moderation Among Adolescents: Evidence from Indonesian Senior High School Students - Darmawansyah Darmawansyah (Department of Social Studies Education, Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University of Palu, Central Sulawesi, Indonesia., 2026)
This study aims to determine the effect of empathy on religious moderation among students at State Senior High School 4 Palu. Religious moderation is crucial for adolescents in fostering attitudes of tolerance, inclusivity, and mutual respect. Furthermore, empathy is an internal psychological factor that warrants further investigation. This study employs a quantitative approach using a survey design. The population consists of 303 students, selected via random sampling with a margin of error of 0.05. The study utilizes the Perth Empathy Scale (PES) to assess empathy levels and religious moderation, focusing on national commitment, tolerance, anti-violence attitudes, and cultural/local accommodation. For data analysis, the researcher used linear regression with SPSS version 20. This study indicates that empathy contributes to religious moderation with a coefficient of 48.91%. This study suggests that fostering empathy in character education is a critical focus that should be prioritized. Additionally, several approaches and methods can be employed in character education, such as experiential learning and reflective learning with a focus on social interaction.